Study of the normalized transverse momentum distribution of W bosons produced in p(p)over-bar collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Agnew, J. P.; Alexeev, G. D.; Alkhazov, G.; Altona, A.; Askew, A.; Atkins, S.; Augsten, K.; et al. (Amer Physical Soc, 2021)
We present a study of the normalized transverse momentum distribution of W bosons produced in p (p) over bar collisions, using data corresponding to an integrated luminosity of 4.35 fb(-1) collected with the D0 detector at the Fermilab Tevatron collider at root s = 1.96 TeV. The measurement focuses on the transverse momentum region below 15 GeV, which is of special interest for electroweak precision measurements; it relies on the same detector calibration methods which were used for the precision measurement of the W boson mass. The measured distribution is compared to different QCD predictions and a procedure is given to allow the comparison of any further theoretical models to the D0 data.